Mathematical Models of the Condition of the Suspension Wire of a New Spatial Rhombic Contact with a Flexible Retainer Taken Into Account of Temperature Changes (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Taking temperature changes into account, the results of creating mathematical models for the states of new spatial rhombic contact suspension wires with flexible fixators will be applicable to all types of spatial rhombic contact suspension wires. It is assumed that all accumulated vertical and horizontal forces act at a single point in the middle of the span, influencing the supporting cables. The goal of creating the mathematical model for this situation is to pre-determine the failure, maintenance, and repair times of the new spatial rhombic contact suspension wires with flexible fixators, as well as to prevent accidents caused by external temperature effects.